New financing trends in Latin America: An overview of selected issues and policy challenges - Camilo E. Tovar; Myriam Quispe-Agnoli (Economic Review, 2008)
During the past fifteen years, financial markets in Latin America have experienced a major transformation. This process and its effects on the nature of risks and policy challenges in Latin America were the focus of a May 2007 conference in Mexico City sponsored by the Representative Office for the Americas of the Bank for International Settlements and the Americas Center of the Federal Reserve Bank of Atlanta. This article summarizes the papers presented at the conference as well as the discussions among participants from central banks, finance ministries, multilateral institutions, academia, and the private sector. In the first conference session, participants examined the shift from crossborder financing toward domestic financing, which has allowed domestic capital markets to expand and become deeper, more diversified, and less dependent on bank financing. The development of domestic bond markets and the resulting policy challenges were the focus of two conference sessions. Issues discussed included the benefits for sovereigns of issuing in local currency, the pros and cons of doing so in domestic vis-à-vis international markets, the criteria for determining whether to issue domestically or cross-border, the status of private markets, the role of structured finance, and whether developing these markets remains a policy objective for de-dollarizing the region's economies. In the final sessions, participants debated the implications that new financial markets have for monetary policysuch as markets' effect on policy transmission and the authorities' role in developing these marketsand for financial stability.
Keywords: E44; E52; F34; G32; H63; O54; 330; domestic capital markets; bond markets; cross-border financing; monetary transmission mechanism; debt financing; debt management; Finanzmarkt; Rentenmarkt; Geldpolitik; Transmissionsmechanismus; Lateinamerika